FORMAL SOURCES OF INTERNATIONAL TRADE LAW. SPECIAL VIEW ON CUSTOM - NIȚĂ, Manuela (International Journal of Legal and Social Order, 2022)
In a period of time where the legal norm sought to cover by regulation all the fields of society, it could easily think that the custom has lost its relevance and its approach could only be done from a historical perspective. Such a conception is wrong because even at this time the customs have a special practical utility and even if they are apparently not widely used in business, it is necessary to know the rules regarding their operation and the effects they produce in the relations between the parties. The customary norm does not exclude the legal norm, they coexist in a relationship of complementarity. These are the basic parameters that form the basis of the present study through which we will analyze the custom and its role as a formal source in the regulation of international trade relations.